Reproductive Performance of the Ardennaise Chicken Breed under Traditional and Modern Breeding Management Systems - Lariviere, J- M.; Michaux, C.; Farnir, F.; Detilleux, J.; Verleyen, V.; Leroy, P. (International Journal of Poultry Science, 2009)
Enhancing the use of traditional chicken breeds is necessary to insure long-term conservation of global genetic diversity in poultry. A logical start in this process is to evaluate performance. The objective of this study was to estimate reproductive traits in the Ardennaise chicken breed under traditional and modern management systems. Reproductive performance indicated lighting programs [Natural (NAT) or Artificial (ART) day length] were highly significant for egg weight, hatchability (p